2020
DOI: 10.3389/fphys.2020.01028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper and Lower Limb Plyometric Training Program on Components of Physical Performance in Young Female Handball Players

Abstract: This study examined the effects of a 10-week combined upper and lower limb plyometric training (ULLPT) programs on components of physical performance in young female handball players. Methods: Participants aged 15.8 ± 0.2 years were randomly assigned between the experimental (EG; n = 17) and control (CG; n = 17) groups. Two-way analyses of performance (group × time) assessed changes in handgrip force, back extensor strength; medicine ball throwing, 30-m sprint times, change of direction (CoD) [Modified Illinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 44 publications
(67 reference statements)
2
44
1
1
Order By: Relevance
“…It seems that the reasons, as demonstrated in female volleyball players [46], are that these differences may be directly related to neuromechanical adaptations because of the repeated actions taking place in training and matches. However, it has also been shown that the results of these tests improved, and therefore, improving physical abilities (jumping, reaction speed, and running speed), when a Plyometric Training Program training was performed [21,22]. This data is of special interest for all the coaches.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It seems that the reasons, as demonstrated in female volleyball players [46], are that these differences may be directly related to neuromechanical adaptations because of the repeated actions taking place in training and matches. However, it has also been shown that the results of these tests improved, and therefore, improving physical abilities (jumping, reaction speed, and running speed), when a Plyometric Training Program training was performed [21,22]. This data is of special interest for all the coaches.…”
Section: Discussionmentioning
confidence: 83%
“…One of these tests is the Yo-Yo Intermittent Recovery Test Level 1 [13], widely applied in recent decades by researchers in indoor handball [14][15][16][17][18][19][20]. Another of the tests, the use of which is widespread, is the Abalakov Jump Test, used to determine the lower body power and fatigue of athletes [21][22][23][24]. In this case, we used the research of Sánchez-Sáez et al [7] as a reference study of BH, which determined that there were no significant decreases in jumping ability during the tournament in female beach handball players (p > 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two studies were included for qualitative assessment: (Witzke and Snow, 2000 ; Myer et al, 2006 ; McLeod et al, 2009 ; Asadi and Arazi, 2012 ; Asadi, 2013 ; Chaouachi et al, 2014a , b ; Faigenbaum et al, 2014 ; Huang et al, 2014 ; Piirainen et al, 2014 ; Asadi et al, 2015 ; Ramírez-Campillo et al, 2015a , b ; Trecroci et al, 2015 ; Benis et al, 2016 ; Karadenizli, 2016 ; Kim and Park, 2016 ; Hopper et al, 2017 ; Nobre et al, 2017 ; Arabatzi, 2018 ; Makhlouf et al, 2018 ; Ritzmann et al, 2018 ; Alikhani et al, 2019 ; Cherni et al, 2019 ; Hammami et al, 2019a , b , c , 2020a , b , c ; Jlid et al, 2019 , 2020 ; Lovecchio et al, 2019 ; Meszler and Váczi, 2019 ; Tay et al, 2019 ; Akin and Kesilmiş, 2020 ; Bouteraa et al, 2020 ; Cigerci and Genc, 2020 ; Drouzas et al, 2020 ; Lee et al, 2020 ; Surakhamhaeng et al, 2020 ; Porrati-Paladino and Cuesta-Barriuso, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the reporting of adverse health effects of PJT, 12 studies (Myer et al, 2006 ; Ramírez-Campillo et al, 2015a , b ; Benis et al, 2016 ; Nobre et al, 2017 ; Makhlouf et al, 2018 ; Hammami et al, 2019b , c , 2020a , b , c ; Jlid et al, 2019 ) reported no adverse health events due to PJT. Two studies (Kim and Park, 2016 ; Porrati-Paladino and Cuesta-Barriuso, 2021 ) reported drop outs due to injuries.…”
Section: Resultsmentioning
confidence: 99%
“…HMB has a positive impact on the body by decreasing the effectiveness of intracellular proteolytic pathways and enhancing the membrane integrity of myocytes, such as the sarcolemma. HMB forms a partnership with a protein called ubiquitin because of its antagonistic effect on protein breakdown processes [101][102][103]. Activation of the mTOR kinase pathway by HMB, on the other hand, can contribute to muscle protein anabolism by boosting the transcription level of the insulin-like growth factor-1 (IGF-1) gene [101].…”
Section: Exercise-induced Muscle Damage Strengthening and Hmbmentioning
confidence: 99%